Analysis of the Effect of Cross-sectional Area on Water Flow Velocity by Using Venturimeter Tubes - Ana Dhiqfaini Sultan; Rizky Rizky; Hidayat Hidayat; Sri Mulyani; Wahdah Anugrah Yusuf (Jurnal Pendidikan Fisika, 2020)
This simple experiment with title  the analysis of the effect of cross-sectional area on air flow velocity using a venturimeter tube with aim to know the relation between section wide, speed of water flow and water level in capillary pipes and to know basic principle of Bernoulli and the application in simple set. The activity was reading water level of capillary pipes the caused by changes of water flow that started from heavy, medium, and low. Then analyzed the data that got for every changes of water flow that started from count the different water level in capillary pipes on big pipes and small pipes after that looking for speed of fluid flow on both pipes. Based on analyze data as a result relation between section wide, speed of water flow and water level in capillary pipes that was as bigger of section wide then the speed of water flow was getting smaller and the level water in capillary pipes was getting taller. This is appropriate with Bernoulli principle that states an increase in the speed of a fluid on a pipe with decrease in pressure and in reverse.Keywords: Venturimeter Tube, Cross-Sectional Area, Speed Of Water Flow, Water Level, Principle Of BernoulliEksperimen sederhana ini berjudul analisis pengaruh luas penampang terhadap kecepatan aliran air dengan menggunakan Tabung Venturimeter yang bertujuan untuk mengetahui hubungan antara luas penampang, Kecepatan aliran air dan ketinggian air pada pipa kapiler serta untuk mengetahui prinsip dasar hukum Bernoulli dan penerapannya dalam rangkaian sederhana. Kegiatan yang dilakukan adalah membaca ketinggian air pipa kapiler yang disebabkan dari perubahan laju aliran air dimulai dari deras, sedang dan rendah. Kemudian menganalisis data yang diperoleh untuk setiap perubahan laju aliran air yang dimulai dari menghitung perbedaan ketinggian air pipa kapiler pada pipa besar dan pipa kecil setelah itu mencari kecepatan aliran fluida pada kedua pipa. Berdasarkan analisis data diperoleh hubungan antara luas penampang, kecepatan aliran air dan ketinggian air pada pipa kapiler yakni semakin besar luas penampang pipa maka kecepatan aliran air pada pipa semakin kecil dan ketinggian air pada pipa kapiler semakin tinggi. Hal ini sesuai dengan bunyi asas Bernoulli yang menyatakan bahwa semakin besar kecepatan fluida dalam suatu pipa maka tekanannya makin kecil dan sebaliknya makin kecil kecepatan fluida dalam suatu pipa maka semakin besar tekanannya.Kata kunci: Tabung Venturimeter, Luas Penampang, Kecepatan aliran air, Ketinggian air, hukum Bernoulli